Hematite pellet with shell-core structure, preparation method and application thereof
Patent Information
- Application Number
- CN202611069846.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-17
- Publication Date
- 2026-10-30
AI Technical Summary
[0010]针对高赤铁矿球团因导热不均和晶格畸变导致的还原剥落、还原膨胀指数高以及膨润土依赖性强的问题,本发明提供一种壳-芯结构高赤铁矿球团矿、制备方法及应用,通过原料功能分区、非对称造球、瞬时热激与原位矿相重构,实现高赤铁矿球团强度、品位与抗还原膨胀性能的协同提升,并大幅降低对膨润土的依赖
(1)抑制还原剥落,显著降低还原膨胀指数:通过在球团外壳中原位生成镁铁尖晶石骨架,在赤铁矿颗粒之间形成连续网状镁铁尖晶石相结构,物理限制赤铁矿在高温还原气氛下的晶格畸变空间,阻断了微裂纹的萌生与扩展。这从物理机制上彻底解决了传统球团易膨胀、粉化剥落的缺陷,大幅降低还原粉末率,显著改善高炉料柱透气性。
Smart Images

Figure CN123005091A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of iron and steel metallurgical pellet production technology, specifically relating to a shell-core structure high hematite pellet, its preparation method, and its application. Background Technology
[0002] In the production of high-proportion hematite pellets, with the depletion of high-quality magnetite resources, the proportion of hematite in the pellet feedstock has generally increased to over 65% in industrial production. Typical minerals include high-grade imported hematite such as P2FG, PFC1, and IOC6. However, hematite and magnetite have significant differences in physicochemical properties, leading to a series of insurmountable technical bottlenecks in the production and application of high-hematite pellets.
[0003] Pellet quality problems caused by inherent defects in hematite Hematite (Fe2O3) belongs to the hexagonal crystal system, has a dense crystal structure and low thermal conductivity, and undergoes lattice distortion (Fe2O3→Fe3O4) under high-temperature reducing atmospheres, accompanied by volume expansion. This problem is particularly prominent in high-hematite pellets: Reduction spalling: During the reduction process in the blast furnace, the surface hematite of the pellets undergoes a phase transformation and expansion, which leads to microcracks on the surface of the pellets and eventually spalls off, forming a large amount of powder, which seriously deteriorates the permeability of the blast furnace.
[0004] Narrow consolidation window: The recrystallization and consolidation of hematite are extremely sensitive to temperature. In traditional processes, temperature fluctuations exceeding ±15℃ will result in over-melting or under-melting, making process control extremely difficult.
[0005] Bentonite dependence: In order to ensure the strength and bursting temperature of green pellets, 2% to 3% of bentonite must be added, which directly leads to an increase in SiO2 content and a decrease in total iron (TFe) grade in the pellets.
[0006] Current cognitive limitations and technological biases in the application of laterite nickel ore To reduce production costs, the industry has experimented with adding laterite nickel ore to pellets. However, existing technologies generally employ a homogeneous mixing process and suffer from the following deeply ingrained technological biases: Uniform mixing bias: The industry generally believes that raw materials must be uniformly mixed to ensure the consistency of pellet composition and structure, and has never considered achieving structural functionalization through asymmetric distribution.
[0007] Mild roasting bias: To prevent the violent decomposition of crystal water in laterite nickel ore from causing pellet bursting, a mild and stable heating curve is usually adopted to avoid high-temperature shock. Especially for the pellet shell, it is generally believed in the industry that high temperatures will cause surface cracking, therefore the use of instantaneous high-temperature treatment is strictly prohibited.
[0008] Limited selection of minerals: Laterite nickel ore has a high content of Al2O3, MgO and alkali metals. It is generally believed in the industry that adding a large proportion will cause reduction expansion and reduction pulverization. Therefore, it is usually only used as a small amount of nickel-containing waste (the amount added is usually ≤1.0%) and is not regarded as a functional material to improve the microstructure of pellets.
[0009] In summary, existing technologies have consistently failed to break free from the traditional approach of uniform mixing, gentle roasting, and the use of magnesia fluxes, and exhibit significant technological biases in their application to laterite nickel ore. Therefore, a new method is urgently needed that can overcome these biases and systematically address issues such as the reduction and exfoliation of high-hematite pellets from the perspectives of in-situ mineral reactions and microstructure reconstruction. Summary of the Invention
[0010] To address the problems of reduction spalling, high reduction expansion index, and strong dependence on bentonite caused by uneven thermal conductivity and lattice distortion in high-hematite pellets, this invention provides a shell-core structure high-hematite pellet, its preparation method, and its application. Through functional zoning of raw materials, asymmetric pelletizing, instantaneous thermal shock, and in-situ mineral phase reconstruction, the strength, grade, and resistance to reduction expansion of high-hematite pellets are synergistically improved, while significantly reducing dependence on bentonite.
[0011] To achieve the above objectives, the technical solution of the present invention is as follows: In a first aspect, the present invention provides a shell-core structured high-hematite pellet, comprising a core and an outer shell covering the outer surface of the core; the outer shell has a composite solidified structure composed of hematite grains and ferromagnetic spinel phase; the ferromagnetic spinel phase in the outer shell is distributed in the pore region between the hematite grains and forms a continuous network of reinforcing framework, which physically restricts the lattice distortion space of the hematite grains.
[0012] Furthermore, the core includes magnetite, hematite, and bentonite accounting for 0.1 to 0.5% of the total mass of the core raw materials. The mass of hematite in the core accounts for ≥65% of the total mass of the core raw materials. This part mainly serves to provide high total iron content and good reducibility.
[0013] Furthermore, the outer shell has a thickness of 2-3 mm, and the mass of the magnesium iron spinel phase accounts for 0.5%-1.5% of the total mass of the outer shell.
[0014] Furthermore, the raw materials for preparing the shell include 1.8% to 2.2% of limonite-type laterite nickel ore by mass. This ratio can ensure the in-situ formation of a continuous magnesium-iron spinel phase framework and provide physical support and water retention, while avoiding the risk of low-melting-point silicate glass phase blocking framework development due to excessive addition, as well as the risk of concentrated removal of crystal water causing pellet bursting.
[0015] Furthermore, the chemical composition of the limonite-type lateritic nickel ore meets the following requirements: Al2O3 mass percentage of 8.5%–9.5%, MgO mass percentage of 0.8%–1.0%, SiO2 mass percentage of 3%–4%, S mass percentage of ≤0.20%, and particle size of ≤200 mesh accounting for ≥95%. Strict control of S content is to prevent the formation of low-melting-point sulfide phases during thermal shock, which would affect the strength of the skeleton; limiting the particle size is to ensure that the lateritic nickel ore reacts fully under instantaneous thermal shock and avoid unreacted nuclei.
[0016] Furthermore, the reduction expansion index (RSI) of the pellets is ≤13%, the compressive strength is ≥3400N / pellet, and the powder rate after reduction is ≤2.5% (≤3mm).
[0017] Secondly, the present invention provides a method for preparing shell-core structured high-hematite pellets, comprising the following steps: (1) Preparation of core pellets: The raw materials containing magnetite and hematite are mixed with bentonite to form mother pellets. The particle size of the mother pellets is controlled to be 8-10 mm. (2) Preparation of shell material: Hematite, limonite-type laterite nickel ore and bentonite accounting for 0.5%~1.0% of the total mass of shell material are mixed. The proportion of limonite-type laterite nickel ore is 1.8%~2.2%, and its chemical composition is 8.5%~9.5% by mass of Al2O3, 0.8%~1.0% by mass of MgO, 3%~4% by mass of SiO2, ≤0.20% by mass of S, and the proportion of particles with a size of ≤200 mesh is ≥95%. (3) Coating into spheres: A shell with a thickness of 2-3 mm is formed by simultaneously spray wetting and rolling. (4) Drying and preheating: Feed the green balls into the chain grate machine and control the temperature of the second stage of the preheating fume hood to be 1100℃~1130℃; (5) Instantaneous heat shock: The green pellets are subjected to a high-temperature airflow of 1280℃~1300℃ for 30~60 seconds in an oxidizing atmosphere from the outlet of the chain grate machine to the inlet of the rotary kiln; (6) Calcination: The heat-treated pellets are calcined at a temperature of 1255℃~1265℃ for 20~30 minutes. The kiln head hood temperature is controlled at 960℃~975℃ during the calcination process to obtain high hematite pellets with a shell-core structure.
[0018] Furthermore, the hematite mentioned in steps (1) and (2) is one or more combinations of P2FG, PFC1 and IOC6.
[0019] Furthermore, in step (5), the temperature of the high-temperature airflow in the instantaneous thermal shock treatment is 1290℃~1300℃, and the duration is 40~50 seconds.
[0020] Furthermore, after step (5) and before step (6), there is also a step of using infrared thermometry to measure the surface temperature of the pellets, controlling the surface temperature of the pellets to be above 1270°C before entering the rotary kiln for roasting, ensuring the thermodynamic conditions required for the development of the magnesium iron spinel phase skeleton, preventing microcracks caused by sudden cooling of the pellets, and ensuring the integrity of the outer shell skeleton.
[0021] Thirdly, the present invention provides an application of the shell-core structure high hematite pellets in blast furnace ironmaking, in which the pellets are used as blast furnace feed. With the advantages of the outer shell skeleton and low silicon and high grade, the high-temperature reduction powder rate of the pellets is significantly reduced, and the amount of slag per ton of blast furnace iron is reduced by 8% to 10% compared with the traditional uniform addition of laterite nickel ore pellets, thereby improving permeability and reducing fuel consumption.
[0022] The beneficial effects of the shell-core structure high hematite pellets of the present invention are as follows: (1) Suppressing reduction spalling and significantly reducing the reduction expansion index: By generating a magnesia-iron spinel framework in situ in the pellet shell, a continuous network magnesia-iron spinel phase structure is formed between hematite particles, which physically restricts the lattice distortion space of hematite under high-temperature reducing atmosphere and blocks the initiation and propagation of microcracks. This completely solves the defects of traditional pellets that are easy to expand, pulverize and spall, from a physical mechanism perspective, greatly reduces the reduction powder rate, and significantly improves the permeability of blast furnace charge.
[0023] (2) Significantly reduce the dependence on bentonite and achieve low-silicon, high-grade pellet production: the porous structure of limonite-type laterite nickel ore plays a role in physical support and water retention in the shell, the overall bentonite content is reduced to below 1.0%, the mass percentage of SiO2 in the pellets is reduced by 0.3%~0.6%, and the TFe grade is increased by 0.1%~0.15%.
[0024] The beneficial effects of the method for preparing shell-core structured high-hematite pellets of the present invention are as follows: (1) Eliminating the risk of thermal fluctuations in the application of laterite nickel ore: By controlling the enrichment of laterite nickel ore in the outer shell and subjecting it to instantaneous high-temperature treatment, the residence time of the pellets in the high-temperature zone is precisely controlled by linking the speed of the chain grate machine with the burner load during the treatment process. Under the dual action of oxidizing atmosphere and instantaneous high temperature, the following key reactions occur in the laterite nickel ore in the outer shell: the crystal water is instantly removed, avoiding the risk of ring formation caused by concentrated release in the rotary kiln; MgO in the laterite nickel ore undergoes an in-situ solid-liquid reaction with hematite at the particle contact point, rapidly generating magnesium iron spinel (MgFe2O4).
[0025] (2) Overcoming the bottleneck of narrow consolidation window of hematite: The shell-core structure enables the pellets to form an asymmetric thermal response mode with high-strength outer shell and high-grade inner core. Combined with the instantaneous heat shock treatment at the outlet of the chain grate machine, it effectively alleviates the problems of poor thermal conductivity and large temperature difference between the inside and outside of hematite. Experimental verification shows that the allowable fluctuation range of hematite consolidation temperature in the traditional uniform mixing process is ±15℃, while the allowable fluctuation range of consolidation temperature in the process of this invention is widened to ±25℃: when the roasting temperature fluctuates in the range of 1255℃~1285℃, the compressive strength fluctuation of the finished pellets is ≤120N / pellet, and the RSI fluctuation is ≤0.3%, which greatly improves the process stability and reduces the difficulty of production control.
[0026] (3) Improve the strength of green balls and preheated balls and improve bursting performance: The laterite nickel ore forms a dense particle accumulation structure in the shell, which simultaneously improves the falling strength and compressive strength of green balls. The bursting temperature of preheated balls is ≥500℃, avoiding thermal stress damage during subsequent thermal shock process. This is significantly better than pellets with uniformly added laterite nickel ore, and reduces air leakage and material return in the chain grate machine.
[0027] (4) Compatible with existing high hematite resources and broaden the adaptability of raw materials: This method is applicable to high proportion hematite raw materials such as P2FG, PFC1, and IOC6. It does not require changes to the existing main equipment of chain grate machine-rotary kiln. Industrial application can be achieved by simply adjusting the pelletizing process and thermal regime.
[0028] (5) Optimize the roasting thermal regime to ensure smooth operation and reduce heat consumption: By limiting the roasting temperature to 1255℃~1265℃ and the roasting time to 20~30 minutes, and controlling the kiln head hood temperature during the roasting process to 960℃~975℃, this invention can ensure that the high proportion of hematite in the inner core is fully recrystallized and consolidated, while effectively avoiding the formation of a low melting point glass phase due to overmelting of the laterite nickel ore in the outer shell. This ensures the stability of the overall thermal regime and significantly reduces the system heat consumption.
[0029] (6) Forming a replicable structured pellet preparation paradigm: This invention proposes for the first time a pellet preparation paradigm of functional shell, high-grade core and instantaneous thermal shock, which can be extended to the pellet production of other high-expansion and difficult-to-roast iron ores and has broad industry application prospects.
[0030] Using the shell-core structure high hematite pellets of the present invention in blast furnace ironmaking is beneficial to reducing the powder rate and slag volume in the blast furnace ironmaking process: the pellets prepared by the present invention do not peel off on the surface under the reducing atmosphere of the blast furnace, and the powder rate of ≤3mm after reduction is reduced from 12.3% of conventional pellets to 2.1%, a reduction of 83%; at the same time, thanks to the aforementioned realization of low-silicon high-grade pellets, it is calculated that the slag volume per ton of blast furnace iron is reduced by 8%~10% compared with the traditional pellets uniformly mixed with laterite nickel ore, which significantly improves the permeability of the blast furnace and reduces the pressure difference and fuel consumption. Attached Figure Description
[0031] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, for those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0032] Figure 1 The image shows a 200x magnified microscopic view of the shell of the finished pellet prepared in Example 2 of this invention, revealing a continuous network framework and its dense structure encapsulating hematite grains.
[0033] Figure 2 This is another microscopic local field-view image of the finished pellet shell prepared in Example 2 of the present invention, magnified 200 times, which further confirms the uniform distribution characteristics of the dense structure covered by the intercrystalline network.
[0034] Figure 3 This is a high-magnification microscopic local morphology image (500x magnification) of the shell of the finished pellet prepared in Example 2 of the present invention, which enhances the display of the details of the grain boundary bonding between the framework phase and the hematite grains. Detailed Implementation
[0035] To enable those skilled in the art to better understand the technical solutions of this invention, the technical solutions of the embodiments of this invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this invention, and not all embodiments. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort should fall within the scope of protection of this invention.
[0036] The methods and standards for testing the physicochemical properties of the finished pellets involved in the various embodiments and comparative examples of this invention are as follows: (1) Test of compressive strength of finished pellets: The test was conducted in accordance with the national standard "Physical Test Method for Iron Ore Pellets" (GB / T14201). A certain number of finished pellets were randomly selected, and the maximum load during fracturing was determined using a pellet compressive strength tester. The average value was taken as the compressive strength of a single pellet (unit: N / pel).
[0037] (2) Reduction expansion index (RSI) test: The test was conducted in accordance with the national standard "Determination of Reduction Expansion Index of Iron Ore" (GB / T 13240). The pellet sample was placed in a reduction tube at 900℃, and a reducing gas (a mixture of CO and N2 in a certain proportion) was introduced and reduced at a constant temperature for a certain period of time. The volume change rate of the pellet sample before and after reduction was measured.
[0038] (3) Powder content test after reduction (low-temperature reduction pulverization): The test was conducted according to the national standard "Static Method for Low-Temperature Reduction Pulverization Test of Iron Ore" (GB / T 13241). After reducing the pellet sample in a specific reducing atmosphere at 500℃ for 1 hour, it was placed in a standard drum and rotated 300 times at a speed of 30 r / min. Subsequently, it was sieved, and the percentage of powder with a particle size ≤3 mm in the total mass of the sample was calculated.
[0039] (4) Evaluation method for compressive strength fluctuation and RSI fluctuation (temperature sensitivity test): Within the set calcination temperature range, different temperature points are selected for calcination and sample preparation. Then, the compressive strength and reduction expansion index (RSI) of the finished pellets obtained at each temperature point are tested using the methods described in (1) and (2) above. The so-called "compressive strength fluctuation" and "RSI fluctuation" refer to the difference between the maximum and minimum values measured between the test groups within the set temperature range.
[0040] Example 1 1. Preparation of core pellets: The raw materials containing magnetite, P2FG, PFC1 and IOC6 combined hematite raw materials are mixed with bentonite to form mother pellets. The particle size of the mother pellets is controlled to be 8-10 mm, and the mass of hematite accounts for ≥65% of the total mass of the core raw materials. 2. Preparation of shell material: Hematite, limonite-type lateritic nickel ore, and bentonite accounting for 0.5% of the total mass of the shell material are mixed. The proportion of limonite-type lateritic nickel ore is 1.8%, and its chemical composition includes Al2O3 at a mass percentage of 8.5%~9.5%, MgO at a mass percentage of 0.8%~1.0%, SiO2 at a mass percentage of 3%~4%, S at a mass percentage of ≤0.20%, and a particle size of ≤200 mesh accounting for ≥95%. 3. Coating into spheres: A 2-3mm thick outer shell is formed by simultaneously spray wetting and spheroidizing. 4. Drying and preheating: The composite green pellets are fed into the chain grate machine for drying and preheating. The temperature of the second stage of preheating is controlled at 1100℃~1130℃ to remove the internal moisture of the green pellets and obtain preliminary strength.
[0041] 5. Instantaneous heat shock treatment: The preheated green pellets enter the front end or high-temperature zone of the rotary kiln and undergo instantaneous heat shock treatment in an oxidizing atmosphere. The treatment temperature is 1280℃, and the treatment time is 30 seconds.
[0042] 6. Conventional roasting: After instantaneous heat shock, the pellets enter the conventional roasting section of the rotary kiln. The roasting temperature is 1255℃~1266℃, and the roasting time is 20~30 minutes. During the roasting process, the kiln head hood temperature is controlled at 960℃~975℃ to ensure the final solidification of the pellets.
[0043] 7. Performance testing of finished pellets The finished pellets obtained through the above process fully embody the core design of this invention, and their specific characteristics and properties are as follows: A distinct shell-core structure is visible upon cross-section. The finished pellets have a compressive strength of 3450 N / pellet; a reduction expansion index (RSI) of 12.5%; and a powder content of ≤3 mm after reduction of 2.3%. All indicators are superior to conventional high-hematite pellets, effectively suppressing reduction spalling.
[0044] Example 2 1. Preparation of core pellets: The raw materials containing magnetite, P2FG, PFC1 and IOC6 combined hematite raw materials are mixed with bentonite to form mother pellets. The particle size of the mother pellets is controlled to be 8-10 mm, and the mass of hematite accounts for ≥65% of the total mass of the core raw materials. 2. Preparation of shell material: Hematite, limonite-type lateritic nickel ore, and bentonite accounting for 0.75% of the total mass of the shell material are mixed. The proportion of limonite-type lateritic nickel ore is 2.0%, and its chemical composition includes Al2O3 at a mass percentage of 8.5%~9.5%, MgO at a mass percentage of 0.8%~1.0%, SiO2 at a mass percentage of 3%~4%, S at a mass percentage of ≤0.20%, and a particle size of ≤200 mesh accounting for ≥95%. 3. Coating into spheres: A 2-3mm thick outer shell is formed by simultaneously spray wetting and spheroidizing. 4. Drying and preheating: The composite green pellets are fed into the chain grate machine for drying and preheating. The temperature of the second stage of preheating is controlled at 1100℃~1130℃ to remove the internal moisture of the green pellets and obtain preliminary strength.
[0045] 5. Instantaneous heat shock treatment: The preheated green pellets enter the front end or high-temperature zone of the rotary kiln and undergo instantaneous heat shock treatment in an oxidizing atmosphere. The treatment temperature is 1290℃, and the treatment time is 45 seconds.
[0046] 6. Conventional roasting: After instantaneous heat shock, the pellets enter the conventional roasting section of the rotary kiln. The roasting temperature is 1255℃~1266℃, and the roasting time is 20~30 minutes. During the roasting process, the kiln head hood temperature is controlled at 960℃~975℃ to ensure the final solidification of the pellets.
[0047] 7. Performance testing of finished pellets The finished pellets obtained through the above process fully embody the core design of this invention, and their specific features and properties are as follows: A distinct shell-core structure is visible upon cross-section; structural features can be observed by combining microscopic morphology: [Example...] Figure 1 and Figure 2 As shown (200x field of view for different areas of the same sample), a large-scale, uniform, dark-colored, continuous network of magnesium-iron spinel reinforcing framework is formed throughout the outer shell. This network framework tightly wraps the light-colored hematite grains, forming a typical dense intergranular network structure; as shown... Figure 3High magnification (500x) further revealed that the dark skeletal phase and the light hematite phase were clearly demarcated and tightly bound together.
[0048] Physicochemical properties: The compressive strength of the finished pellets reaches 3520 N / pellet; the reduction expansion index (RSI) is reduced to 11.8%; and the powder content ≤3mm after reduction is only 2.1%. Blast furnace application shows that no surface spalling occurred, significantly improving the permeability of the blast furnace charge.
[0049] Example 3 1. Preparation of core pellets: The raw materials containing magnetite, P2FG, PFC1 and IOC6 combined hematite raw materials are mixed with bentonite to form mother pellets. The particle size of the mother pellets is controlled to be 8-10 mm, and the mass of hematite accounts for ≥65% of the total mass of the core raw materials. 2. Preparation of shell material: Hematite, limonite-type lateritic nickel ore, and bentonite accounting for 1.0% of the total mass of the shell material are mixed. The proportion of limonite-type lateritic nickel ore is 2.2%, and its chemical composition includes Al2O3 at a mass percentage of 8.5%~9.5%, MgO at a mass percentage of 0.8%~1.0%, SiO2 at a mass percentage of 3%~4%, S at a mass percentage of ≤0.20%, and a particle size of ≤200 mesh accounting for ≥95%. 3. Coating into spheres: A 2-3mm thick outer shell is formed by simultaneously spray wetting and spheroidizing. 4. Drying and preheating: The composite green pellets are fed into the chain grate machine for drying and preheating. The temperature of the second stage of preheating is controlled at 1100℃~1130℃ to remove the internal moisture of the green pellets and obtain preliminary strength.
[0050] 5. Instantaneous heat shock treatment: The preheated green pellets enter the front end or high-temperature zone of the rotary kiln and undergo instantaneous heat shock treatment in an oxidizing atmosphere. The treatment temperature is 1300℃ and the treatment time is 60 seconds.
[0051] 6. Conventional roasting: After instantaneous heat shock, the pellets enter the conventional roasting section of the rotary kiln. The roasting temperature is 1255℃~1266℃, and the roasting time is 20~30 minutes. During the roasting process, the kiln head hood temperature is controlled at 960℃~975℃ to ensure the final solidification of the pellets.
[0052] 7. Performance testing of finished pellets: The finished pellets obtained through the above process fully embody the core design of this invention, and their specific characteristics and properties are as follows: A distinct shell-core structure is visible upon cross-section; the compressive strength of the finished pellets is increased to 3610 N / pellet; the reduction expansion index (RSI) is further reduced to 11.2%; and the powder content ≤3mm after reduction is only 1.8%. The structure is highly stable, fully meeting the stringent requirements for furnace charge strength in large blast furnace smelting.
[0053] To verify the necessity of the process parameters and the significant technical advantages of the present invention, the following control experiments were conducted. Except for adjusting the corresponding parameters, all other conditions in all experiments were consistent with the process in Example 2 above: Comparative Example 1: Standard Uniform Mixing The core and shell materials of Example 2 were mixed and pelletized in one step, without two-step pelletizing or instantaneous heat shock. Results: The finished pellets had a compressive strength of 3220 N, RSI of 11.1%, SiO2 content of 7.85%, a preheated pellet burst temperature of only 420℃, and a powder rate of ≤3mm after reduction of 12.3%. All properties of Example 2 were significantly better than those of the comparative example.
[0054] Comparative Example 2: Boundary Verification of Laterite Nickel Ore Proportioning ① Discontinuation of laterite nickel ore addition: The proportion of laterite nickel ore added to the outer shell was adjusted to 0. Due to the loss of the magnesium-iron spinel phase structure, the grade of the pellets plummeted to 62.97%, SiO2 rebounded to 7.85%, and the strength of the preheated pellets fluctuated, proving the significant effect of adding laterite nickel ore in Example 2.
[0055] ② 2.5% ratio group: The proportion of laterite nickel ore added to the outer shell was adjusted to 2.5%. Results: After instantaneous thermal shock, the outer shell showed obvious overmelting. Microscopic morphology observation showed that the continuity of the framework was destroyed. The excessive laterite nickel ore introduced Al2O3 and SiO2, forming a large amount of low-melting-point silicate glass phase, filling the pores and blocking the development of the framework. The compressive strength of the finished pellets was 3120N, and the RSI was 14.8%, which did not meet the requirement of less than or equal to 13%, proving that the technical solution of Example 2 has significant advantages. ③ 3.0% ratio group: The ratio of laterite nickel ore in the outer shell was adjusted to 3.0%. Results: The crystal water in the preheating section was concentratedly removed, the pellet bursting temperature dropped to 380℃, and the bursting rate reached 12%; after roasting, the outer shell showed large-area peeling, and no continuous network skeleton structure was observed in the microstructure; the compressive strength of the finished pellets was 2850 N, and the RSI was 15.3%, indicating severe performance degradation, which further verified the significant effect of the scheme in Example 2.
[0056] Comparative Example 3: Boundary Verification of Instantaneous Thermal Shock Parameters ① Temperature below the lower limit group: The instantaneous thermal shock temperature was reduced to 1250℃ (lower than the lower limit of 1280℃ in this invention). Results: Microscopic morphology observation showed that no continuous spinel framework was formed on the surface of the pellets, and only a small number of isolated particles were observed; the RSI rebounded to 14.5%, proving that the instantaneous thermal shock above 1280℃ in Example 2 is a necessary condition for the formation of the magnesium-iron spinel phase.
[0057] ② Time below the lower limit group: The speed adjustment of the chain grate machine shortened the instantaneous thermal shock time to 20 s (below the lower limit of 30 s in this invention). Results: The shell temperature only rose to 1180℃, the MgO in the laterite nickel ore was not fully activated, and no continuous network skeleton was observed in the microstructure; the RSI of the finished pellets was 13.9%, exceeding the control threshold of 13%, and the compressive strength was 3310 N, lower than the 3400 N achieved in Example 2, proving the significant advantage of the scheme in Example 2.
[0058] ③ Time Exceeding the Upper Limit Group: The speed of the chain grate machine was adjusted to extend the instantaneous thermal shock time to 70 s (exceeding the upper limit of 60 s in this invention). Results: The shell temperature rose to 1320℃, and the hematite was over-sintered to form a continuous glassy phase, hindering the diffusion of reducing gas; the powder rate of ≤3mm was measured to be 16.2%, which is significantly higher than that of Example 2; the compressive strength of the finished pellets was 3200 N, and the performance decreased, proving the significant advantage of the scheme in Example 2.
[0059] Comparative Example 4: Consolidation Window Verification Temperature sensitivity tests were conducted on the same chain grate-rotary kiln equipment: In the traditional uniform mixing process, when the calcination temperature fluctuated by ±15℃, the compressive strength fluctuated by 280 N / ball and the RSI fluctuated by 0.8%; In Example 2, within the calcination temperature range of 1255~1285℃ (fluctuation ±25℃), the compressive strength fluctuated by only 92 N / ball and the RSI fluctuated by only 0.23%, which fully demonstrates the technical effect of widening the consolidation window of Example 2 from the traditional ±15℃ to ±25℃.
[0060] Although the invention has been described in detail with reference to the accompanying drawings and preferred embodiments, the invention is not limited thereto. Various equivalent modifications or substitutions can be made to the embodiments of the invention by those skilled in the art without departing from the spirit and essence of the invention, and all such modifications or substitutions should be within the scope of the invention.
Claims
1. A shell-core structured high-hematite pellet, characterized in that, It includes a core and an outer shell covering the outer surface of the core; the outer shell has a composite solidified structure composed of hematite grains and ferromagnetic spinel phase; the ferromagnetic spinel phase in the outer shell is distributed in the pore region between the hematite grains and forms a continuous network of reinforcing skeleton.
2. The shell-core structured high-hematite pellets according to claim 1, characterized in that, The core comprises magnetite, hematite, and bentonite comprising 0.1 to 0.5% of the total mass of the core raw materials, wherein the mass of hematite in the core comprises ≥65% of the total mass of the core raw materials.
3. The shell-core structured high-hematite pellets according to claim 1, characterized in that, The outer shell has a thickness of 2-3 mm, and the mass of the magnesium iron spinel phase accounts for 0.5%-1.5% of the total mass of the outer shell.
4. The shell-core structured high-hematite pellets according to claim 1, characterized in that, The raw materials for preparing the shell include 1.8% to 2.2% of the total mass of the shell raw materials, which is the limonite-type laterite nickel ore.
5. The shell-core structured high-hematite pellets according to claim 1, characterized in that, The chemical composition of the goethite-type laterite nickel ore meets the following requirements: Al2O3 mass percentage of 8.5% to 9.5%, MgO mass percentage of 0.8% to 1.0%, SiO2 mass percentage of 3% to 4%, S mass percentage of ≤0.20%, and particle size of ≤200 mesh accounting for ≥95%.
6. The shell-core structured high-hematite pellets according to any one of claims 1 to 5, characterized in that, The pellets have a reduction expansion index (RSI) ≤ 13%, a compressive strength ≥ 3400 N / pellet, and a powder content of ≤ 3 mm after reduction of ≤ 2.5%.
7. A method for preparing shell-core structured high-hematite pellets according to any one of claims 1 to 6, characterized in that, Includes the following steps: (1) Preparation of core pellets: The raw materials containing magnetite and hematite are mixed with bentonite to form mother pellets. The particle size of the mother pellets is controlled to be 8-10 mm. (2) Preparation of shell material: Hematite, limonite-type laterite nickel ore and bentonite accounting for 0.5%~1.0% of the total mass of shell material are mixed. The proportion of limonite-type laterite nickel ore is 1.8%~2.2%, and its chemical composition is 8.5%~9.5% by mass of Al2O3, 0.8%~1.0% by mass of MgO, 3%~4% by mass of SiO2, ≤0.20% by mass of S, and the proportion of particles with a size of ≤200 mesh is ≥95%. (3) Coating into spheres: A shell with a thickness of 2-3 mm is formed by simultaneously spray wetting and rolling. (4) Drying and preheating: Feed the green balls into the chain grate machine and control the temperature of the second stage of the preheating fume hood to be 1100℃~1130℃; (5) Instantaneous heat shock: The green pellets are subjected to a high-temperature airflow of 1280℃~1300℃ for 30~60 seconds in an oxidizing atmosphere from the outlet of the chain grate machine to the inlet of the rotary kiln; (6) Calcination: The heat-treated pellets are calcined at a temperature of 1255℃~1265℃ for 20~30 minutes. The kiln head hood temperature is controlled at 960℃~975℃ during the calcination process to obtain high hematite pellets with a shell-core structure.
8. The method according to claim 7, characterized in that, In steps (1) and (2), the hematite is one or more combinations of P2FG, PFC1 and IOC6; more preferably, in step (5), the temperature of the high-temperature gas flow in the instantaneous thermal shock treatment is 1290℃~1300℃, and the duration is 40~50 seconds.
9. The method according to claim 7, characterized in that, Between steps (5) and (6), there is also a step of using infrared thermometry to monitor the surface of the pellets online, and controlling the surface temperature of the pellets to be above 1270°C before entering the rotary kiln.
10. The application of a shell-core structured high-hematite pellet as described in any one of claims 1 to 6 or a shell-core structured high-hematite pellet obtained by any one of claims 7 to 9 in blast furnace ironmaking.
